Education strategies in engaging business towards syariah compliance in As-Sofa Islamic College - Ahmad Razimi, Mohd Shahril; Abdul Rahim, Ahmad Khilmy (MAXWELL Science Publication, 2016)
In the 20th, fundamental Islamic business witnessed resurgence practices around the world from the observation. However, the fact that business capitalism under unbridled and cannot be denied that Muslim world remains far from the Islamic ideal.Widening rapidly the gap between the reality and the ideal and the well being of the masses has become a threat also to the stability and very peace of Muslim societies.This case study is to describe business entity based on Sharia compliance.Business characteristics and the concept of business will present as a basic understanding. Sharia compliance will be explores in form of business management model.Five aspects of business entity will be proposed a model of business in Sharia compliance on this study; the function of management, the process of business, corporate culture, corporate governance and corporate social responsibility that will be implemented by As-Sofa Islamic college.